The Judge's Refusal of The Application for Marriage Dispensation - Amirah, Nabilla; Eva, Yusnita (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
A phenomenon revealed that there is a conflict between the objectives of the maqashid syari'ah and the decision of the Pangkajene Religious Court judge No.0228/PDT.P/2020/PA.PKJ in the case of a marriage dispensation application. The purpose of maqashid syari'ah in the dispensation of marriage is to avoid adultery that enters the maintenance of religion (Hifz al-Din). The marriage dispensation was proposed by the parents as applicants because their children have often gone out together and even had intercourse as husband and wife but this was rejected by the judge. The problem above is the goal to explain legal considerations by the judge of the Pangkajene Religious Court in the application for marriage dispensation and maqasid al-syari'ah review of the decision of the judge in the application for marriage dispensation. This research used a library research method by citing the contents of the judge's determination files and books related to the problem under study and the data used is in the form of secondary data, namely in the form of decisions of the Religious Courts. The fact is that in this stipulation the judge rejected the application for marriage dispensation by not considering the immoral acts that had been committed by the prospective groom and prospective bride. Furthermore, the purpose of maintaining religion in this determination is not fulfilled where the judge uses the method of avoiding mafsadah taking precedence over bringing maslahah as if contrary to the stipulation in which the judge rejects the proposed marriage dispensation application.